Clinical Evidence of Herbal Drugs As Perpetrators of Pharmacokinetic Drug Interactions - Hermann, Robert; von Richter, Oliver (Planta Medica, 2012)
The use of herbal/botanical products, also referred to as complementary and alternative medicines (CAM), worldwide enjoys increasing popularity. It appears in particular highly prevalent in patient populations already exposed to complex treatment algorithms and polypharmacotherapy, frequently involving narrow therapeutic index drugs. Accordingly, the potential clinical dimension and relevance of herb-drug interactions has received considerable attention over the last years. However, review of pertinent literature indicates that the available clinical evidence in this regard is still limited and sometimes inconclusive. Also, communication of herb-drug interaction data in the biopharmaceutical/medical literature is often complex and confusing, not always unbiased, and in many cases appears not to strive for clear-cut and useful guidance in terms of the clinical relevance of such findings.This systematic review summarizes and interprets the published evidence on clinical herb-drug interaction studies which examined the potential of six popular herbal drugs (Echinacea, garlic, gingko, ginseng, goldenseal, and milk thistle) as perpetrators of pharmacokinetic (PK) drug interactions. Reported effect sizes were systematically categorized according to FDA drug interaction guideline criteria. A total of 66 clinical PK interaction studies, meeting the scope of the present review, were identified. The clinical evidence was found to be most robust and informative for Gingko biloba (GB; 21 studies) and milk thistle/silymarin (MT; 13), and appears still limited for ginseng (9), goldenseal/berberine (GS; 8), garlic (8), and Echinacea (7). Collectively, the available evidence indicates that, at commonly recommended doses, none of these herbs act as potent or moderate inhibitors or inducers of cytochrome P450 (CYP) enzymes or P-glycoprotein (ABCB1). Weak effects in terms of either induction or inhibition were found for GB (presystemic/hepatic CYP3A4 induction/inhibition, CYP2C19 induction at high doses), milk thistle/silymarin (CYP2C9 inhibition), GS/berberine (CYP3A4 and CYP2D6 inhibition), Echinacea (presystemic/hepatic CYP3A4 inhibition/induction, CYP1A2 and CYP2C9 inhibition at high doses). Information was found not always complete for the major drug metabolizing CYP enzymes in the less well-studied herbs and is largely limited to P-glycoprotein (ABCB1) when effects on drug transporters have been investigated.
Keywords: herbal drugs; botanical drugs; complementary and alternative medicines; drug interactions; pharmacokinetics